Telerheumatology during the COVID-19 pandemic: Impact on clinical practice, education, and research - Su Ann Yeoh; Anastasia-Vasiliki Madenidou (Indian Journal of Rheumatology)
Telerheumatology, the use of telemedicine in the provision of rheumatology care, has been on the periphery of rheumatology practice for several years. However, the need for remote rheumatology service has emerged during the COVID-19 pandemic in order to help prevent the spread of the virus. EULAR and ACR published guidelines to address the rheumatological clinical needs safely. Synchronous and asynchronous telemedicine, including remote patient-monitoring systems, were used. The majority of telerheumatology studies focus on rheumatoid arthritis, which is reflective of the caseload in the rheumatology clinic. Connective tissue diseases are likely to pose more challenges for telemedicine use, given its multi-organ involvement and heterogeneity. The benefits of telemedicine include patient safety, minimizing travel time and time off work, and the evidence of patient satisfaction has supported this. On the other hand, the lack of clinical examination and privacy is a concern which patients might have about receiving telerheumatology care. Physicians are more comfortable providing telemedicine consultations for already-established patients, especially those with stable disease, and less with new patients. Rheumatology training has been disrupted, and rheumatology trainees were required to rapidly adapt their practices to telemedicine as outpatient clinics transitioned to virtual clinics. Tele-education and virtual rheumatology conferences have enabled education to be delivered in a more inclusive way. In conclusion, it is likely that hybrid models will be adopted for patient care after the pandemic. However, it is imperative that the patient is at the center of future telerheumatology service design.